Express Delivery and Logistics Courier Company Marketing Analysis (Case Study: JNE) - Ikhtiara, Syehani Haura; Adinira, Millenia; Handayani, Serina Putri; Nugraheni, Esti Ayu (Universitas Diponegoro, 2023)
JNE is a company engaged in the delivery of goods in Indonesia. Goods delivery is not only done within the country but also provides overseas goods delivery services. PT JNE Express has an extensive network and professional services that have helped in product distribution and increased competitiveness in marketing. Freight forwarding service companies have specific marketing strategies in capturing markets and competing for customers with different marketing strategies, strategies and determining the right marketing mix will make it easier for companies to create, build and carry out good marketing strategies. This study aims to find out how the marketing strategy is implemented in PT JNE Express.This study uses a qualitative descriptive method approach. Description method to explain aspects related to research collected through literature study. This study uses research journals, books, theses, and trusted online news channel sources to collect data, reduce and search for and select variable descriptions.Based on the results of marketing strategy research conducted by PT JNE Express, namely using the application of segmenting, targeting, positioning and marketing mix. This strategy has superior products that suit customer needs which include good service and information communication and the process strategy includes fast and precise technology-oriented contact service services.